Studies related to osteosarcoma and metabolism from 1990 to 2022: A visual analysis and bibliometric study - Shao, Zhuce; Bi, Shuxiong (Frontiers in Endocrinology, 2023)
Background The material and energy metabolism of tumor cells depends to a large extent on neuroendocrine regulation, so it is of great scientific and clinical importance to analyze the relationship and mechanisms between tumors such as osteosarcoma and metabolic processes. The abnormal metabolic processes of tumor cells are one of the difficult pathological mechanisms in malignant tumors. Among them, the development and progression of osteosarcoma cannot be separated from the endocrine regulation of tumor cells and their various metabolic processes. In many cancer types, metabolic processes are important for tumor growth progression, so interfering with the metabolic processes of osteosarcoma may be a therapeutic option to stall osteosarcoma progression. A key mechanism of how metabolic processes contribute to the growth and survival of various cancers, including osteosarcoma, is their ability to support tumor cell metabolism. Research related to this field is a direction of great importance and potential. However, to our knowledge, no bibliometric studies related to this field have been published, and we will fill this research gap. Results Based on the search strategy, 833 articles were finally filtered. In this area of research related to osteosarcoma metabolism, we found that China, the United States and Japan are the top 3 countries in terms of number of articles published, and the journals and institutions that have published the most research in this area are Journal of bone and mineral research, Shanghai Jiao Tong University. In addition, Baldini, nicola and Reddy, Gs are the top three authors in terms of number of articles published in studies related to this field. The most popular keywords related to the field in the last 30 years are "metabolism" and "expression", which will guide the possible future directions of the field. Conclusion We used Bibliometrix, VOSviewer, and Citespace to visualize and bibliometrically analyze the current status and possible future hotspots of research in the field of osteosarcoma metabolism. Possible future hotspots in this field may focus on the related terms "metabolism", "expression", and "migraation".